2014
DOI: 10.1111/psyp.12235
|View full text |Cite
|
Sign up to set email alerts
|

The temporal course of the influence of anxiety on fairness considerations

Abstract: This study investigated the potential causes of anxious people's social avoidance. The classic ultimatum game (UG) was utilized in concert with electroencephalogram (EEG) recording. Participants were divided into two groups according to levels of trait anxiety as identified by a self-report scale. The behavioral results indicate that high-anxious participants were more prone to reject human-proposed than computer-proposed unequal offers compared to their low-anxious counterparts. The event-related potential (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
73
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 63 publications
12
73
0
1
Order By: Relevance
“…In the social domain, previous research also showed that violation of the social norm would give rise to larger FRN amplitude [911,21]. Although non-binding in nature, compliance with the commitment was generally deemed as a social norm, and failing to do so would be regarded as a severe violation of the norm, which might lead to the commitment effect in the non-reward condition in the current study.…”
Section: Discussionsupporting
confidence: 50%
“…In the social domain, previous research also showed that violation of the social norm would give rise to larger FRN amplitude [911,21]. Although non-binding in nature, compliance with the commitment was generally deemed as a social norm, and failing to do so would be regarded as a severe violation of the norm, which might lead to the commitment effect in the non-reward condition in the current study.…”
Section: Discussionsupporting
confidence: 50%
“…In this sample, individuals with STAI-T scores in the upper 25% of the distribution were considered as high-trait anxiety subjects4950 and passed into a second-level screen. Among the high-trait anxiety sample, individuals with BDI-II scores ≤13 were labeled as nondepressed subjects, whereas individuals scored >13 in BDI-II were labeled as depressed subjects.…”
Section: Methodsmentioning
confidence: 99%
“…The P3 is a centro‐parietal positivity that appears after the FRN when elicited by outcome feedback (Polezzi, Sartori, Rumiati, Vidotto, & Daum, 2010; Wu & Zhou, 2009; Zhang et al., 2013). When investigating feedback processing, the P3 is often associated with the emotional significance of outcome feedback (Gu et al., 2011; Luo et al., 2014; Wu & Zhou, 2009). Both the FRN and the P3 have been reported to be sensitive to the degree of information uncertainty, but it is unclear whether they reflect different aspects of ambiguous feedback processing (Ernst & Steinhauser, 2015; Gibbons, Schnuerch, & Stahl, 2016; Hirsh & Inzlicht, 2008; Polezzi et al., 2008; Polich, 1990).…”
Section: Introductionmentioning
confidence: 99%